Abbreviation Used by Indonesian K-Pop Fans on Twitter - Euis Meinawati; Maylinda Vina Violita; Octa Pratama Putra; Herlin Widasiwi Setianingrum; Sufi Alawiyah; Chodidjah Chodidjah (Universitas Hamzanwadi, 2021)
The purpose of the study was to get deeply information abbreviation usage in Twitter application. The abbreviation has used to make shorter time in delivering the message but the receiver can understand the message. The method used descriptive qualitative. The data is taken from www.twitter.com as an online application. The source of data was the Twitter application that has made by university students, high school students and employee. The study found that 4 types of abbreviation have used in twitter communication, namely clipping, blending, acronym, and initialism. The abbreviation usage helps the people to make simple conversation like as non-formal communication.